A Study On Outbreak Of Malarial Fever Among The Residents Of Village Mandal Of Taluka Viramgam, Distt. Ahmedabad, Gujarat - Lala M.K (Wolters Kluwer Medknow Publications, 1989)
Outbreak of malaria had occurred in the months of September to November 1988 amongst the residents of village mandal, taluka viramgam, district ahmedabad. As compared to September-November 1987, significant increase in annual blood examination rate (ABER) and slide positivity rate (SPR) was observed in 1988 (September-November). 88 deaths occurred due to malaria from August to December 1988. Mortality rate was more amongst children and people of the lower class. Case fatality rate (CFR) was maximum (11.45%) in October 1988. But due to intensive measures it decreased to 1.47% in December 1988. Appearance of breeding places of mosquitoes due to heavy rains after three consecutive droughts, inadequate surveillance, mosquito resistance to insecticides, plasmodium resistance to drug treatment may have led to this outbreak amongst the residents of village mandal.